2012
DOI: 10.1210/jc.2012-2538
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Vitamin D Concentration on Fetal Bone

Abstract: Using a novel method for assessing FV, independent predictors of femoral size were maternal height, adiposity, and serum vitamin D. Future trials should establish whether pregnancy supplementation with vitamin D is beneficial for the fetal skeleton, using FV and PMD as fetal outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 24 publications
2
67
0
Order By: Relevance
“…These studies have examined associations between estimated maternal intake of vitamin D or single measurements of maternal 25-hydroxyvitamin D during pregnancy, and various skeletal outcomes in the offspring. In agreement with data from observational studies and randomized trials discussed above, there were no significant associations found with weight, skeletal lengths, or bone mineral density at birth (281,285,363,399,460,713).…”
Section: Associational Studiessupporting
confidence: 87%
See 2 more Smart Citations
“…These studies have examined associations between estimated maternal intake of vitamin D or single measurements of maternal 25-hydroxyvitamin D during pregnancy, and various skeletal outcomes in the offspring. In agreement with data from observational studies and randomized trials discussed above, there were no significant associations found with weight, skeletal lengths, or bone mineral density at birth (281,285,363,399,460,713).…”
Section: Associational Studiessupporting
confidence: 87%
“…However, left unstated in the abstract was that the association was not statistically significant after correcting for gestational age of the babies. (281). Maternal 25-hydroxyvitamin below 75 nM was associated with slightly smaller femur length, width, and volume, an association that is in the opposite direction from the original report by Mahon and co-workers (281).…”
Section: Associational Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…There are inconsistent data on the association between maternal serum 25OHD levels and linear growth during the first year of life [152,[156][157][158] and insufficient to weak evidence for an association between maternal serum 25OHD levels and bone mass or density at birth [150,[159][160][161][162] or in later childhood [158,163,164] . …”
Section: Evidencementioning
confidence: 99%
“…Using 3D ultrasound, it is possible to measure not only the FL but also its volume (FV) [5], and this may have the theoretical advantage of allowing a more detailed assessment of femoral size. It has recently been shown that maternal vitamin D insufficiency is associated with reduced FV [6], although there is no significant correlation with FL [6,7]. …”
Section: Introductionmentioning
confidence: 99%